(untitled) (Ameghiniana, 2017)
Here we describe the first record of Incamys bolivianus for Patagonia, in the Late Oligocene locality of Cabeza Blanca (Sarmiento Formation; Chubut Province, Patagonia, Argentina). This specimen documented by a partial mandible, clearly confirms the presence of the species in southern South America, since only some doubful reports were available so far. Incamys bolivianus is the first shared species between Salla-Luribay (Bolivia) and Patagonia (Argentina) fauna.